Organizational performance in the post-COVID-19 era: The predictors’ impacts - Foluso Philip Adekanmbi; Wilfred Isioma Ukpere (Problems and Perspectives in Management, 2022)
This paper assesses the impacts of teleworking, perceived technostress, and job insecurity on the organizational performance (OP) of Nigeria’s business organizations in the post-COVID-19 era. The sample was obtained from 10 business organizations in the Oyo and Lagos States of Nigeria. This investigation espoused a cross-sectional scientific study involving surveys. In the current investigation, survey forms were randomly distributed among 300 employees. Of the 300 surveys floated, 277 were fitting for scrutiny and analyzed using Statistical Packages for Social Sciences (SPSS version 28). The current study established a positive impact of teleworking on organizational performance. Besides, it showed a substantial negative impact of technostress on organizational performance. It further noted that perceived job insecurity negatively affects organizational performance.Moreover, this study showed a significant joint strong influence of teleworking, technostress, and job insecurity on the organizational performance of Nigeria’s business organizations in the post-COVID-19 era. Thus, management should encourage the work practice that allows employees to work at the agreed location since findings indicated a substantial and positive influence of teleworking on organizational performance in the post-COVID-19 era. Besides, employers need to increase their workers’ capability for information technology-enabled creativeness to mitigate the negativity generated by technostress. Also, management should ensure that employees have access to information, constantly communicate, and participate in organizational processes to better overcome perceived insecurity and emotional distress. Furthermore, the information and communication must hint at the prospect and stability of post-COVID-19 services. Consequently, employees’ perceptions of organizational identification are promoted. AcknowledgmentWe acknowledge the Department of Industrial Psychology and People Management, College of Business and Economics, University of Johannesburg, under Professor Wilfred Isioma Ukpere, for funding this study and its publication.